2015
DOI: 10.1093/eurpub/ckv063
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Greek herbal tea consumption on thyroid cancer: a case-control study

Abstract: Our findings suggest for the first time that drinking herbal teas, especially chamomile, protects from thyroid cancer as well as other benign thyroid diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…From these 16 articles, nine were excluded due to the following reasons: one study did not consider thyroid cancer as an outcome, two studies did not assess coffee as an exposure, one study did not provide calculable information for the OR, four studies were review articles, and one case-control study involved thyroid cancer patients for both the case group (anaplastic thyroid cancer) and the control group (papillary cancer). Therefore, seven articles were included in the meta-analysis [18,19,20,21,22,23,24] (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…From these 16 articles, nine were excluded due to the following reasons: one study did not consider thyroid cancer as an outcome, two studies did not assess coffee as an exposure, one study did not provide calculable information for the OR, four studies were review articles, and one case-control study involved thyroid cancer patients for both the case group (anaplastic thyroid cancer) and the control group (papillary cancer). Therefore, seven articles were included in the meta-analysis [18,19,20,21,22,23,24] (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…One of the most popular functional beverages is herbal teas (Xuetao, 2015) derived from plants other than Camellia sinensis (Poswal et al, 2019). Herbal teas are beneficial for the maintenance of diabetes (Ryan et al, 2000;Jayawardena et al, 2005;Zemestani et al, 2016), cholesterol level and blood pressure (McKay and Blumberg, 2006;McKay et al, 2010), even for reducing the risk of thyroid cancer (Riza et al, 2015). Liquid-based herbal infusions offered an ideal medium for water-soluble phytochemicals (i.e.…”
Section: Problem Statements and Research Purposesmentioning
confidence: 99%
“…As a type of functional food, one of its most important objective quality attributes was health benefit (Astrini et al, 2020). In previous studies, herbal teas were said to be helpful for the maintenance of diabetes (Jayawardena et al, 2005;Zemestani et al, 2016), cholesterol level and blood pressure (McKay and Blumberg, 2006;McKay et al, 2010), and the risk level of thyroid cancer (Riza et al, 2015). This study used four indicators to measure health belief.…”
Section: Variables and Indicatorsmentioning
confidence: 99%
“…A pioneering study in the mid-1990s summarized the available epidemiologic information and found that tea consumption is likely to have beneficial effects on reducing the cancer risk in some people [1]. Recently, a meta-analysis found an inverse association between tea consumption and cancer risk [4,58,59,60,61]. However, some evidence does not support the hypothesis that tea can reduce the risk of cancer [62,63].…”
Section: Tea Resists Carcinogenesismentioning
confidence: 99%